2020
DOI: 10.3390/ijerph17072430
|View full text |Cite
|
Sign up to set email alerts
|

A New Application of Social Impact in Social Media for Overcoming Fake News in Health

Abstract: One of the challenges today is to face fake news (false information) in health due to its potential impact on people's lives. This article contributes to a new application of social impact in social media (SISM) methodology. This study focuses on the social impact of the research to identify what type of health information is false and what type of information is evidence of the social impact shared in social media. The analysis of social media includes Reddit, Facebook, and Twitter. This analysis contributes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
111
0
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(140 citation statements)
references
References 48 publications
0
111
0
9
Order By: Relevance
“…These results are consistent with the study conducted by Brennen et al (2020), as they found a strong significant correlation between Social Media platforms (Facebook, YouTube & Twitter) and fake news. Also validated by Pulido, Ruiz-Eugenio, et al (2020), as they stated that although globalization plays a vital role in spreading healthcare information, Social Networking platforms also contain misinformation. Covid-19 is a dominant part of online discourse, and harmful, personal, and opinionated content adversely affects the current situation.…”
Section: Discussionmentioning
confidence: 97%
“…These results are consistent with the study conducted by Brennen et al (2020), as they found a strong significant correlation between Social Media platforms (Facebook, YouTube & Twitter) and fake news. Also validated by Pulido, Ruiz-Eugenio, et al (2020), as they stated that although globalization plays a vital role in spreading healthcare information, Social Networking platforms also contain misinformation. Covid-19 is a dominant part of online discourse, and harmful, personal, and opinionated content adversely affects the current situation.…”
Section: Discussionmentioning
confidence: 97%
“…However, misinformation spread through the internet can hinder the communication of health entities and professionals with the general population (Lu & Zhang, 2019) and so reduce adherence to the confrontations proposed to contain the pandemic, as social distancing (Farooq et al, 2020). Research on the role of internet content, social media messages and dominant discourses that are communicated to the public is an emerging topic of public health interest in scientific work that requires further investigation (Pulido et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Fake news and misinformation concerning health on the Research, Society and Development, v. 9, n. 12, e3591210680, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i12.10680 internet represents a threat to global health (Carrieri et al, 2019). The World Health Organization (WHO) warned that the COVID-19 outbreak had been accompanied by a massive abundance of information, some of which was accurate and some of which was not, which made it difficult for people to find reliable sources and trustworthy information when they needed it (Kouzy et al, 2020;Pulido et al, 2020). The consequences of disinformation overload are the spread of uncertainty, fear, anxiety and racism.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, it is the direct consumer of the information who must filter and screen which news he or she decides to believe and which not (see Aleixandre-Benavent et al, 2020). The problem is that not everyone has sufficient skill and knowledge to effectively screen information (see Pulido et al, 2020a). In fact, Pulido et al (2020b) observed that fake news is "tweeted" or disseminated more on social networks than scientifically-based information.…”
Section: Introductionmentioning
confidence: 99%